The Eurasian Economic Union as an Element of the Belt and Road Initiative - Czerewacz‑Filipowicz, Katarzyna (Comparative Economic Research. Central and Eastern Europe, 2019)
The New Silk Road, or actually the Belt and Road Initiative (BRI), is a Chinese concept aimed at facilitating international trade between China, Europe and Africa as well as building a new international economic order and security system. More than 60 countries belonging to various economic groupings with different levels of economic development and economic openness have been involved in the BRI. Many branches of the BRI run through the countries belonging to the Eurasian Economic Union (EAEU). This is mainly the Trans‑Siberian corridor, being the northern branch of the Route, which is being developed in the most dynamic way and is the most exploited among all railway connections between China and Europe. In theory, the EAEU and its customs union between Belarus, Kazakhstan and Russia should allow the easy transit of goods between Europe and Asia. Transport infrastructure, much better than in the case of the other BRI railway branches, seems to be an additional advantage. Unfortunately, political and structural factors, as well as the embargo imposed by Russia on many goods originating in Western Europe, significantly limit the possibilities of using this transport route. The aim of the article is to examine the potential of the Eurasian Economic Union as part of the Belt and Road Initiative and assess the possibility of using the transport corridor running through the territory of the EAEU within the BRI. We will also identify the main determinants that will affect the development of transport and logistics corridors running through the EAEU in the future.